The influence of pre-warming on the physiological responses to prolonged intermittent exercise - Gregson, W. A.; Batterham, A.; Drust, B.; Cable, N. T. (Journal of Sports Sciences, 2005)
To examine the influence of pre-warming on the physiological responses to prolonged intermittent exercise in ambient temperatures of 21.5 ± 0.6°C and relative humidities of 35.7 ± 5.4% (mean ± s), six healthy men performed intermittent treadmill running (30-s bouts at 90% of maximal oxygen uptake separated by 30-s static recovery periods) to exhaustion after active pre-warming, passive pre-warming and pre-exercise rest (control). Exercise time to exhaustion was significantly different between all conditions (active, 51.8 ± 7.2min; passive, 38.5 ± 11.1min; control, 72.0±17.2?min; P <0.05). These changes in performance time were closely associated with a significant decline in both the rate of heat storage and heat storage capacity (P <0.05). Rectal temperature, heart rate and ratings of perceived exertion were significantly higher during exercise in the two pre-warming conditions than in the control condition (P < 0.05). Ratings of perceived exertion were also significantly higher during exercise following passive pre-warming compared with active pre-warming (P < 0.05). During exercise there were no significant differences in serum prolactin, plasma norepinephrine and plasma free fatty acid concentrations between conditions. We conclude that both active and passive pre-warming promote a reduction in prolonged intermittent exercise capacity in environmental temperatures of 21°C compared with pre-exercise rest. These performance decrements were dependent upon the mode of pre-warming and closely reflected alterations in body heat content.